Graphene aerogel-based catalysts in Fenton-like reactions for water decontamination: a short review - Lingling Wang (Elsevier, 2021)
Fenton-like reactions represent an effective strategy to generate strongly oxidative species for the elimination of refractory organic pollutants in water. In the past decades, many research efforts have been made to the development of heterogeneous catalysts in Fenton-like reaction, in order to address the issues in homogeneous Fenton system, e.g., narrow pH suitability, slow reduction of Fe3+ to Fe2+, and production of iron sludge. Graphene aerogel (GA), with unique π-π conjugated structure and properties, has been widely used in many applications, including as substrate for the preparation of composite catalysts used in various reactions. In this review, we summarize recent studies using GA as substrate for the preparation of heterogeneous catalysts in Fenton-like reactions. We first describe briefly the preparation of GA and GA-based composites. We then separate the examples of GA-based catalysts in three chapters, i.e., in conventional Fenton, photo-Fenton, and electro-Fenton systems. The mechanisms for the enhancement of catalytic reactivity in these Fenton-like systems due to the use of GA are also discussed. In the end, future studies are envisioned.